Carbohydrate and lipid metabolism indices dynamic in patients with postinfarction cardiosclerosis, type 2 diabetes and obesity in 6 months and 1 year after myocardial revascularization - P. P. Kravchun (Zaporožskij Medicinskij Žurnal)
Nowadays conservative therapy and reperfusion techniques, which include thrombolytic therapy and percutaneous coronary intervention considered as the main strategies for the acute coronary syndrome treatment.